2023
DOI: 10.3389/fvets.2023.1195074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tea residues-fermented feed on production performance, egg quality, antioxidant capacity, caecal microbiota, and ammonia emissions of laying hens

Abstract: This study was to assess the effects of tea residues-fermented feed (TR-fermented feed) on production performance, egg quality, serum antioxidant capacity, caecal microbiota, and ammonia emissions of laying hens. A total of 1,296 Lohmann laying hens have randomly distributed four groups with six parallels and fed with diets TR-fermented feed at the rates of 0 (control), 1, 3, and 5%. The inclusion of 1% (TR)-fermented feed resulted in a significant increase in egg-laying rate and average egg weight of birds, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…This could be because the content of various active or nutritional components in the by-products does not reach concentrations that have a noticeable effect (Sarker et al, 2022;Khurana et al, 2023). Previous studies have indicated that the use of tea and its by-products in monogastric animals can significantly improve their production performance, such as increasing egg production rate, egg weight, and other factors (Wang et al, 2018;Chen et al, 2023). However, in this study, no significant impact of DTR on sheep's production performance was observed, which may be attributed to the unique rumen fermentation characteristic of ruminant animals.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because the content of various active or nutritional components in the by-products does not reach concentrations that have a noticeable effect (Sarker et al, 2022;Khurana et al, 2023). Previous studies have indicated that the use of tea and its by-products in monogastric animals can significantly improve their production performance, such as increasing egg production rate, egg weight, and other factors (Wang et al, 2018;Chen et al, 2023). However, in this study, no significant impact of DTR on sheep's production performance was observed, which may be attributed to the unique rumen fermentation characteristic of ruminant animals.…”
Section: Discussionmentioning
confidence: 99%
“…The feed consumption was recorded once a week, and the value of average daily feed intake (ADFI) was calculated. Egg production (EP), average egg weight (AEW), feed to egg ratio (FER) and egg breakage rate (EBR) were calculated for each replicate based on the feeding trial records by referring to the method of Chen et al 15 . and Wang et al 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Supplementation of 1% significantly improved the Haugh unit, whereas 3% improved the content of essential amino acids and total omega-3 polyunsaturated fatty acids in the eggs [141] Corn and soybean meal 250, 750, and 1500 g N.A.…”
Section: The Impact Of Feeding Bioconverted Byproducts On Performance...mentioning
confidence: 95%